2017
DOI: 10.1044/2017_jslhr-s-16-0277
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Suprahyoid Muscles: A Volumetric Musculoaponeurotic Analysis

Abstract: The results suggest that the suprahyoid muscles can have individualized roles in hyoid excursion during swallowing. Muscle balance may be important for identifying and treating hyolaryngeal dysfunction in patients with dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Muscle architecture, an important determinant of function, is the arrangement of the contractile and connective tissue elements within the volume of a muscle. Architectural differences between muscle partitions can be visualized in 3D, at the FB/aponeurosis level, and characterized by quantifiable architectural parameters (Li et al, ; Shaw et al, ). These architectural parameters include: (1) fiber bundle length (FBL), the length of a FB between attachment sites — an indicator of muscle excursion capabilities; (2) pennation angle (PA), the angle of the FB relative to the muscle's line of action — a factor in force generation; (3) physiological cross‐sectional area (PCSA), the sum of cross‐sectional areas of all the FBs within the muscle volume (MV) — a measure of relative force generating capability; (4) line of action (LoA), the direction of the force transmission; and (5) sarcomere length (SL), the distance between two adjacent Z‐lines of a myofibril — additional factor in force generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle architecture, an important determinant of function, is the arrangement of the contractile and connective tissue elements within the volume of a muscle. Architectural differences between muscle partitions can be visualized in 3D, at the FB/aponeurosis level, and characterized by quantifiable architectural parameters (Li et al, ; Shaw et al, ). These architectural parameters include: (1) fiber bundle length (FBL), the length of a FB between attachment sites — an indicator of muscle excursion capabilities; (2) pennation angle (PA), the angle of the FB relative to the muscle's line of action — a factor in force generation; (3) physiological cross‐sectional area (PCSA), the sum of cross‐sectional areas of all the FBs within the muscle volume (MV) — a measure of relative force generating capability; (4) line of action (LoA), the direction of the force transmission; and (5) sarcomere length (SL), the distance between two adjacent Z‐lines of a myofibril — additional factor in force generation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous architectural studies have found that VMO has more horizontally oriented FBs than VML (Lieb and Perry, ; Javadpour et al, ; Hubbard et al, ). Cadaveric studies, to date, investigating VMO/VML architecture have sampled FBs primarily from the superficial surface of the muscle, even though muscle architecture has been shown to vary within the muscle volume (Li et al, ; Shaw et al, ). Studies of VMO and VML have mainly documented PA, with a few studies reporting FBL, PCSA, and other parameters (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the cervical functional spaces, especially between basiocciput and C1, as well as C1 and C2, must be examined thoroughly by the physiotherapist. The normal functional spaces should measure 6.5 ± 2.5 mm [ 18 ]. In the case of decreased spaces, their width should be restored.…”
Section: Discussionmentioning
confidence: 99%
“…Both the movement and the position of the mandible, which is the inferior part of the TMJ, are affected by different muscles, including not only the masticatory muscles (masseter, temporal, lateral pterygoids, medial pterygoid) [ 17 ] and the suprahyoid muscles (digastric, mylohyoid, geniohyoid) [ 18 ], but also the superior pharyngeal constrictor muscle [ 19 ]. The superior pharyngeal constrictor muscle has been found to have four parts of the origin (pteropharyngeal, buccopharyngeal, mylopharyngeal, and glossopharyngeal), and only one insertion at the posterior pharyngeal wall [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Architectural parameters include fiber bundle length (FBL), a measure of relative excursion capability; pennation angle (PA), a factor influencing force generation; muscle volume (MV), the size of a muscle; and physiological cross-sectional area (PCSA), the relative force generating capability of the muscle. [10,11] Five cadaveric studies were found that investigated the architectural parameters of the great toe musculature (Table 1). Kura et al, [12] Silver et al [13] and Tosovic et al [14] sampled 3 fiber bundles in each great toe muscle, whereas Lachowitzer et al [15] and Ledoux et al [16] did not report the number of FBs sampled.…”
Section: Introductionmentioning
confidence: 99%